Adsorption Efficiency of UV-Irradiated Polyvinyl AlcoholAlginate Adsorbent Beads for Chromium (VI) Removal - Lau, W.G; Selimin, M.A; Lee, T.C (uthm, 2025)
Due to the risk of chromium (Cr) contamination, industrial waste emissions have become a global concern, necessitating an effective adsorption approach. Polyvinyl alcohol (PVA) - alginate beads are a promising material for overcoming this problem. The present work aims to investigate the effect of ultraviolet (UV) light irradiation on the preparation of PVA-alginate beads throughout a range of UV irradiation durations, as well as its Cr (VI) removal rate. In this work, a homogeneous gel made of PVA and sodium alginate (SA) was produced and then radiated to UVA light for varying periods of time (5-20 minutes). Subsequently, the PVA-alginate adsorbent beads were made by crosslinking with 6% boric acid and 2% calcium chloride. PVAalginate adsorbent beads were fabricated easily after UVA irradiation because the viscosity of gel PVA-alginate was reduced. The Cr (VI) adsorption experiment employed 15 g of PVA-alginate adsorbent beads, 180 minutes of adsorption time, and 50 mg/L Cr (VI) initial concentration. The size analysis revealed that the average diameter of the adsorbent beads after Cr (VI) adsorption was approximately 4.00 mm. The UV-Vis results showed that sample A prepared by exposing the PVA-alginate adsorbent beads to UV light for 5 minutes has an optimum Cr (VI) removal rate of 71.63% after in contact for 180 minutes. This study's findings were critical for establishing a new knowledge of the production of PVA-alginate beads irradiated with UV light and moving forward to mitigate heavy metal pollution in waste water, therefore enhancing the quality of water and the environment.